2008
DOI: 10.1016/j.ydbio.2008.02.030
|View full text |Cite
|
Sign up to set email alerts
|

The canonical Wnt signaling antagonist DKK2 is an essential effector of PITX2 function during normal eye development

Abstract: Local control of cell signaling activity and integration of inputs from multiple signaling pathways are central for normal development but the underlying mechanisms remain poorly understood. Here we show that Dkk2, encoding an antagonist of canonical Wnt signaling, is an essential downstream target of the PITX2 homeodomain transcription factor in neural crest during eye development. Canonical Wnt signaling is ectopically activated in central ocular surface ectoderm and underlying mesenchyme in Pitx2- and Dkk2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
158
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(170 citation statements)
references
References 87 publications
(116 reference statements)
11
158
1
Order By: Relevance
“…Whereas lack of the Wnt antagonist Dkk2 resulted in the ectopic appearance of conjunctiva, epidermis and hair follicles in the corneal epithelium due to direct and/or indirect effect (Mukhopadhyay et al, 2006;Gage et al, 2008), we did not observe these phenotypes in our animal model, regardless of the initial time of Dox-treatment to induce expression of E3-catenin in K12-positive corneal epithelial cells. One of the possibilities is that Wnt/-catenin activation in the Dkk2 null-mutant affects corneal epithelial stem and/or progenitor cells, whereas only the K12-positive cells (including differentiating -or transient amplifying cells -and differentiated corneal epithelial cells) are influenced in our mouse model.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Whereas lack of the Wnt antagonist Dkk2 resulted in the ectopic appearance of conjunctiva, epidermis and hair follicles in the corneal epithelium due to direct and/or indirect effect (Mukhopadhyay et al, 2006;Gage et al, 2008), we did not observe these phenotypes in our animal model, regardless of the initial time of Dox-treatment to induce expression of E3-catenin in K12-positive corneal epithelial cells. One of the possibilities is that Wnt/-catenin activation in the Dkk2 null-mutant affects corneal epithelial stem and/or progenitor cells, whereas only the K12-positive cells (including differentiating -or transient amplifying cells -and differentiated corneal epithelial cells) are influenced in our mouse model.…”
Section: Discussioncontrasting
confidence: 70%
“…Repression of the Wnt/-catenin signaling pathway has been implicated as an essential prerequisite for the differentiation of corneal epithelial progenitor cells into a non-keratinizing stratified epithelium during corneal morphogenesis (Mukhopadhyay et al, 2006;Gage et al, 2008). It has been previously shown that stabilized E3-catenin driven by the Le-Cre promoter suppresses surface ectoderm invagination for lens formation at ~E9.5 tõ E10.5.…”
Section: Discussionmentioning
confidence: 99%
“…Besides MAP3K1, embryonic eyelid closure depends on signals derived from WNT, Sonic hedgehog, BMP/Activin, FGF and EGF (Luetteke et al, 1993;Mine et al, 2005;Gage et al, 2008;Huang et al, 2009). In addition, eyelid closure requires the participation of a number of intracellular signaling kinases, such as JNK, ROCK and CDH1, and nuclear transcription factors, such as c-Jun, Fra-2, FOXL2, SMAD and GRHL3 (McHenry et al, 1998;Li et al, 2003;Zenz et al, 2003;Zhang et al, 2003;Uda et al, 2004;Thumkeo et al, 2005;Takatori et al, 2008;Yu et al, 2008;Naoe et al, 2010).…”
Section: Map3k1 In Ocular Surface Developmentmentioning
confidence: 99%
“…It has been shown that loss of Dkk2, an antagonist of canonical Wnt signaling pathways, suppresses corneal differentiation during mouse development (Gage et al, 2008;Mukhopadhyay et al, 2006). This strongly suggests that canonical Wnt signaling might play a crucial role in ocular surface epithelia development.…”
Section: Introductionmentioning
confidence: 99%